Menemukan Nilai Kepemimpinan Christian Simbar Bagi Wajah Pendeta GKE Masa Kini - Apria Yemima Epipani (Jurnal Teologi Pambelum, 2022)
History is the story of the past that contains a million valuable lessons. It offers a positive note when it flirts with history: learn from history. Indonesia's fight against the dayak people in central kalimantan is one of the most important lessons to learn. Central kalimantan before officially becoming the self-sufficient province has a long labyrinth of history. The fighting spirit of fighters and communities needs to be recognized, understood, and embedded. One of the heroes involved in the establishment of central kalimantan province is Christian Mandolin Simbar or Christian Simbar that leads a movement called the mandau movement of pantja. The leadership of Christian Simbar became an appropriate part of being recognized and understood, and reflected by the GKE's pastor nowadays.